Cannabidiol Inhibits Multiple Ion Channels in Rabbit Ventricular Cardiomyocytes - Isaev, Dmytro; Shabbir, Waheed; Dinc, Ege Y.; Lorke, Dietrich E; Petroianu, Georg; Oz, Murat (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD), a major non-psychotropic cannabinoid found in the Cannabis plant, has been shown to exert anti-nociceptive, anti-psychotic, and anti-convulsant effects and to also influence the cardiovascular system. In this study, the effects of CBD on major ion currents were investigated using the patch-clamp technique in rabbit ventricular myocytes. CBD inhibited voltage-gated Na+ and Ca2+ channels with IC50 values of 5.4 µM and 4.8 µM, respectively. In addition, CBD, at lower concentrations, suppressed ion currents mediated by rapidly and slowly activated delayed rectifier K+ channels with IC50 of 2.4 µM and 2.1 µM, respectively. CBD, up to 10 µM, did not have any significant effect on inward rectifier IK1 and transient outward Ito currents. The effects of CBD on these currents developed gradually, reaching steady-state levels within 4 to 7 min., and recoveries were usually slow and partial. Hill coefficients higher than unity in concentration-inhibition curves suggested multiple CBD binding sites on these channels. These findings indicate that CBD affects cardiac electrophysiology by acting on a diverse range of ion channels and suggest that caution should be exercised when CBD is administered to carriers of cardiac channelopathies or to individuals using drugs known to affect the rhythm or the contractility of the heart.